A Lorenz/Boer energy budget for the atmosphere of Mars from a "reanalysis" of spacecraft observations - Tabataba-Vakili, F; Read, P; Lewis, S; Montabone, L; Ruan, T; Wang, Y; Valeanu, A; Young, R (American Geophysical Union, 2015)
We calculate a Lorenz energy budget for the Martian atmosphere from reanalysis derived from Mars Global Surveyor data for Mars years 24-27. We present global, annual mean energy and conversion rates per unit area and per unit mass and compare these to Earth data. The directions of the energy conversion terms for Mars are similar to Earth, with the exception of the barotropic conversion between zonal and eddy kinetic energy reservoirs. Further, seasonal and hemispheric decomposition reveals a strong conversion between zonal energy reservoirs over the year, but these balance each other out in global and annual mean. On separating the diurnal timescale, the contribution to the conversion terms and eddy kinetic energy for diurnal and shorter timescales in many cases (especially during planet-encircling dust storms) exceeds the contribution of longer timescales. This suggests that thermal tides have a significant effect on the generation of eddy kinetic energy. Key Points Comprehensive analysis of global and hemispheric energy exchanges within the Mars atmosphere Thermal tides have a significant impact on eddy energy and conversion terms Most conversion occurs in zonal component but is canceled out in annual and global mean